Aktivitas Antiinflamasi In Vitro dan In Vivo Ekstrak Etanol Daun Mangga Arumanis (Mangifera indica L.): In Vitro and In Vivo Anti-Inflamatory Activities of Ethanol Extract Mangifera indica L. Leaves - Sholihatil Hidayati; Firda Oktavianti; Dhina Ayu Susanti; Qurrotul Aini (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Inflammation is a normal process designed to protect oneself and promote healing of body tissues. The mechanism of action of flavonoids as antiinflammatory is through the inhibition of arachidonic acid and the secretion of lysosomal enzymes. The ethanol extract of Mangifera indica L. leaves (EEML) contains flavonoids and is widely used as a medicine empirically. This study was conducted to evaluate the antiinflammatory effect of EEML in vitro and in vivo. In vitro study of the antiinflammatory activity of EEML based on its effect on the stability of blood membranes using UV-Vis spectrophotometry method. While the in vivo activity was tested using the carrageenan induction method on white rats of the Wistar strain. In vitro activity was expressed as EC50 and in vivo activity was expressed as % edema reduction. The results showed that ethanol extract was able to increase membrane stability with an EC50 value of 8.56 ?g/ml better than positive control aspirin with EC50 21.57 ?g/ml. In vivo test results showed that the administration of EEML doses of 200 mg/kg.bw, 400 mg/kg.bw, and 800 mg/kg.bw was not significantly different from the positive control in reducing edema. EEML has shown antiinflammatory effects in vitro and in vivo, so it has the potential to be developed as an antiinflammatory agent.